ISOLASI DAN KARAKTERISASI ENZIM BROMELIN DARI BUAH NANAS (Ananas comosus L.) - Elina Putri, Elina (Journal of Technique Research (JTR), 2019)
Lowry isolation and test have been carried out on the enzyme activity of bromelin from pineapple. In this study bromelin in isolation using extraction method using distilled water using 1: 1 w / w, which is then determined by activity (tilapia substrate) and finding the level of protein by Lowry method with a spectrophotometer with a variation of 0 minutes, 5 minutes, 15 minutes and 25 minutes. The isolation results obtained were crude bromelin enzyme extracts with a protein content of 0 minutes which was 184,997 ppm indicating that the enzyme had not yet worked. This is widely used to determine the concentration of enzymes. The optimal time for the bromelin enzyme is at 5 minutes.